2021
DOI: 10.1080/15476286.2021.1910403
|View full text |Cite
|
Sign up to set email alerts
|

RGG-motif containing mRNA export factor Gbp2 acts as a translation repressor

Abstract: Complex cascades of RNA-binding proteins regulate the mRNA metabolism and influence gene expression. Several distinct proteins act at different stages of mRNA life cycle. SR family proteins in yeast are implicated in mRNA processing and nuclear export. In this report, we uncover the role of an SR/RGGmotif containing mRNA export factor Gbp2 in mRNA translation regulation. We demonstrate that Gbp2 localizes to cytoplasmic granules upon heat shock and oxidative stress. Our pull-down assays demonstrate that Gbp2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…21 Heat stress also leads to the extensive reprogramming of mRNA processing, export, and translation, with concomitant formation of RNA granules in the cytoplasm. 22 The GO enrichment analysis in this study showed that DEmRNAs are mainly involved in biological processes such as cell cycle regulation, spermatogenesis, and transcriptional regulation, suggesting that CIRBP may influence spermatogenesis by participating in these processes. In addition, CIRBP has been shown to be associated with the cell cycle and spermatogenic functions.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…21 Heat stress also leads to the extensive reprogramming of mRNA processing, export, and translation, with concomitant formation of RNA granules in the cytoplasm. 22 The GO enrichment analysis in this study showed that DEmRNAs are mainly involved in biological processes such as cell cycle regulation, spermatogenesis, and transcriptional regulation, suggesting that CIRBP may influence spermatogenesis by participating in these processes. In addition, CIRBP has been shown to be associated with the cell cycle and spermatogenic functions.…”
Section: Discussionmentioning
confidence: 54%
“…Intracellularly, endoplasmic reticulum stress can be induced by heat stress, and a reduction in CIRBP expression after heat stress may induce this stress by leading to the accumulation of misfolded proteins in the endoplasmic reticulum 21 . Heat stress also leads to the extensive reprogramming of mRNA processing, export, and translation, with concomitant formation of RNA granules in the cytoplasm 22 . The GO enrichment analysis in this study showed that DEmRNAs are mainly involved in biological processes such as cell cycle regulation, spermatogenesis, and transcriptional regulation, suggesting that CIRBP may influence spermatogenesis by participating in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides RNA degradation, Gbp2 and Hrb1 may also serve specific functions in translation repression in NMD. Recent studies demonstrated that Gbp2 and Hrb1 show features similar to a group of yeast RGG motif-containing proteins that act as translation repressors [104,134]. These proteins inhibit translation initiation through their RGG motifdependent interaction with eIF4G, a scaffold protein of the cap-binding eIF4F complex important for eukaryotic translation initiation (reviewed in [128]).…”
Section: Gbp2 and Hrb1 In Nonsense-mediated Mrna Decay-new Cytoplasmic Rolesmentioning
confidence: 99%
“…Recently, it was shown that SRSF1 stimulates NMD by promoting Upf1 binding, and that SRSF2 affects the association of key NMD factors [137,138], demonstrating more direct links between SR proteins and cytoplasmic surveillance. Apart from NMD, Gbp2 can act as a translation repressor [134], whereas some SR proteins were shown to either suppress or enhance the translation of specific mRNAs [139,140]. An additional correlation is provided by the discovery of homologous proteins that phosphorylate these proteins-the yeast kinase Sky1 and its mammalian counterpart SRPK1 [141]-and mediate their import-the import receptors Mtr10 (in yeast) and TRN-SR (in Mammalia), respectively [142].…”
Section: Gbp2 and Hrb1 As Prototypes Of Human Proteinsmentioning
confidence: 99%
See 1 more Smart Citation